Land-use change mapping and analysis using remote sensing and GIS for watershed evaluation- A case study - PUSHPANJALI (Journal of Soil and Water Conservation, 2022)
Watershed development and its management are dynamic with new challenges and complexities, rendering difficulties in laying out a proper development plan. There is a need for an accurate process to assess the progress of implementation. Its assessment and evaluation need a holistic approach through reliable methods. Increasing the number of indigenous remote sensing satellites, reasonable pricing of indigenous satellite data and trained human resources have further facilitated the application of remote sensing for watershed management. In this study, a cluster of five watersheds, three in Telangana State (Mangalagudem, Rampur, Chilkepalli) and two in Andhra Pradesh (R.N. Palle, Nathiobanagari Palle-II) were taken up for watershed evaluation study. A detailed methodology for the impact evaluation of watersheds using remote sensing and geographical information system (GIS) is presented in this paper. Post classification comparison of pre-and post-implementation satellite imagery for watershed is being used for impact evaluation. Land use classification was done using SOI toposheet of 1:25,000 scale and LISS- IV (MS) remote sensing imagery. Results clearly show that interventions to check soil erosion and water run-off in a watershed mode increased Rabi cropped area up to 61 per cent and Kharif cropped area up to 22 per cent in all the watersheds. There was about a 47 per cent decrease in the extended fallow area in Nathiobanagari Palle-II watershed. Thus, interventions for checking soil erosion and runoff lead to the area’s sustainable development in all the evaluated watersheds.